2018
DOI: 10.3389/fpsyg.2018.01732
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and Psychology Student Experiences of Personal Therapy: A Critical Interpretive Synthesis

Abstract: Background: Committing to attendance at personal therapy sessions is frequently either mandated or encouraged in many different types of therapeutic trainings across allied health, psychotherapy, social work and counseling. The small number of published accounts have indicated that student experiences of personal therapy can be mixed.Methods: The project examined contemporary interview based research about student experience of personal therapy during training using Critical Interpretive Synthesis method. Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…The “synthesising argument” of CIS, while derived from a wider body of research, could be at risk of being limited to the kind of conclusions that can be arrived at from standard literature reviews. There are valuable examples of CIS, however, which have assimilated and extended bodies of research using similar methods such as qualitative interviewing (Edwards, 2018), or provided syntheses of less interpretive data such as explicit policy decision-making frameworks (Morgan et al, 2018). Resolving the debate of what research methods can or should be incorporated into meta-ethnography is beyond the scope of this article.…”
Section: Combining Research Methodologiesmentioning
confidence: 99%
“…The “synthesising argument” of CIS, while derived from a wider body of research, could be at risk of being limited to the kind of conclusions that can be arrived at from standard literature reviews. There are valuable examples of CIS, however, which have assimilated and extended bodies of research using similar methods such as qualitative interviewing (Edwards, 2018), or provided syntheses of less interpretive data such as explicit policy decision-making frameworks (Morgan et al, 2018). Resolving the debate of what research methods can or should be incorporated into meta-ethnography is beyond the scope of this article.…”
Section: Combining Research Methodologiesmentioning
confidence: 99%
“…This can be seen as a form of ‘transformative learning' (Mezirow, 1991). Consequently, the PD group has emerged as the default model for facilitating the development of self‐awareness in counselling trainees, although the question of whether personal therapy should be mandatory for counselling trainees has been debated for a number of years (Edwards, 2018; Kumari, 2011; McMahon, 2018). von Haenisch (2011) notes that the BACP dispensed with the requirement in 2005, although Chaturvedi (2013) reported that 50% of courses still required it.…”
Section: Pd Groups and Their Purposementioning
confidence: 99%
“…von Haenisch (2011) notes that the BACP dispensed with the requirement in 2005, although Chaturvedi (2013) reported that 50% of courses still required it. There is still a strong feeling from theoretical and research papers that personal therapy will support trainees in their PD, enhance learning and develop insights about working with the therapeutic process (Edwards, 2018).…”
Section: Pd Groups and Their Purposementioning
confidence: 99%
“…Some have suggested that such experiences can facilitate a therapist’s ability to develop rapport, show empathy, and serve as a model of recovery for clients (e.g., Boyd et al, 2016; Gilroy et al, 2002). In fact, some programs and professional organizations require students to seek personal psychotherapy while in training (Edwards, 2018; Kumari, 2011). On the other hand, others have suggested that personal experiences with mental health concerns, such as depression, may have a negative impact on therapists’ work, such as negatively affecting their ability to concentrate in therapeutic relationships (e.g., Gilroy, Carroll, & Murra, 2001; Gilroy et al, 2002).…”
mentioning
confidence: 99%